Sectoral growth in Chile: 1962-82 - Coeymans, Juan Eduardo; Mundlak, Yair (International Food Policy Research Institute, 1993)
The agricultural share of a country's total output generally declines in the process of economic growth. The major reason for this is that consumer demand for food increases only slightly with rising incomes. However, a small, open economy can overcome this constraint to the growth of agricultural production by expanding its net exports. Chile serves as a good example. Its share of agriculture in total output averaged 9.46 percent during 1986-90, compared with 9.66 percent in 1960-64 9 (Figure 1). The relative long-term constancy of this agricultural share in Chile presents a sharp departure from the experience of most countries. The option of maintaining such a constant share is not open to all countries, but the Chilean experience is of general interest for a variety of cases, as shown in Sectoral Growth in Chile: 1962-82, Research Report 95, by Juan Eduardo Coeymans and Yair Mundlak.